Conceptions and practices in the teaching of English reading in high school - O'Connell, Daniel Mateus; Monteiro, Dirce Charara [UNESP] (Univ Federal Santa Maria, 2016)
Considering the unsatisfactory results regarding the teaching of English reading, as well as the scarcity of research on this theme in high school level, this research aims at identifying the theoretical and methodological conceptions of two high school English teachers about the different approaches to reading and how these conceptions are present in their practice. In this qualitative research data were obtained by observing the teachers' practice and by interviewing both teachers. The results of this research can offer indicators for activities aimed at improving the teaching of reading English as a foreign language.
Keywords: Reading education; High school; English language; Reading strategies; Conceptions and teaching practices